Electrochromic material based on organic framework structure and electrochromic device thereof

By self-assembling the cathode and anode electrochromic functional groups through covalent bonding to form an electrochromic material with a covalent organic framework structure, the shortcomings of existing materials in terms of stability, response speed and service life are solved, and higher performance and wider applications are achieved.

CN119613646APending Publication Date: 2025-03-14NINGBO MI RUO ELECTRONICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411796584.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing electrochromic materials have shortcomings in stability, response speed, service life and environmental adaptability, especially in large-area smart glass devices, there is still room for improvement in reliability and durability.

Method used

By self-assembly reacting the functional groups with cathode electrochromic function and the functional groups with anode electrochromic function through covalent bonding, an electrochromic material with covalent organic framework structure characteristics is formed. This material has both the characteristics of rapid response, while improving the structural stability and service life of the material.

Benefits of technology

Faster color discoloration response, higher contrast, wider color discoloration range and stronger aging resistance, allowing electrochromic devices to maintain good performance after long-term use and are suitable for a variety of smart devices and energy-saving buildings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613646A_ABST
    Figure CN119613646A_ABST
Patent Text Reader

Abstract

The invention relates to an electrochromic material based on an organic framework structure. The electrochromic material is a covalent organic framework material obtained by self-assembly reaction of a functional group with a cathode electrochromic function and a functional group with an anode electrochromic function in a covalent bond combination mode. The electrochromic material based on the organic framework structure has the advantages of high stability, quick response, excellent cycle life and the like. The invention further discloses an electrochromic device comprising the electrochromic material based on the organic framework structure. The electrochromic device can be widely applied to intelligent glass devices such as automobile rearview mirrors, automobile windows, airplane portholes and building glass curtain walls.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochromism, and in particular to an electrochromic material based on an organic skeleton structure and an electrochromic device thereof. Background Art

[0002] With the rapid development of modern science and technology, electrochromic materials have attracted extensive attention due to their unique optical and electrochemical properties. These materials can change their color and transparency by applying voltage, thus showing great application potential in energy efficiency, privacy protection and aesthetic design. Traditional electrochromic materials mainly include inorganic oxides such as WO3, NiO, etc., and organic polymers such as polythiophene and viologen derivatives. These materials have been reported and applied in smart windows, anti-glare rearview mirrors, displays and other electronic devices.

[0003] However, electrochromic materials in existing technologies still face some challenges and limitations. For example, inorganic materials usually have problems with complex processing, high cost and poor flexibility, while organic materials may perform poorly in terms of stability, response speed and cycle life. Especially in large-area smart glass devices that require long-term stable operation, the reliability and durability of existing materials and devices still need to be improved. In addition, the performance degradation of these devices in environments such as extreme temperature, humidity and ultraviolet radiation also needs to be solved urgently. In order to overcome these limitations, researchers are actively exploring the design of new electrochromic materials and devices in order to achieve better performance and a wider range of applications. Although there has been some research progress, electrochromic technology still needs to achieve further breakthroughs in materials science, device engineering and manufacturing processes to meet the market's growing demand for high-performance, low-cost and environmentally friendly electrochromic devices. Summary of the invention

[0004] In view of the above shortcomings of the prior art, the present invention provides an electrochromic material based on an organic skeleton structure to solve the problems of existing electrochromic materials in terms of stability, response speed, service life and environmental adaptability. Through innovative structural design, the electrochromic material of the present invention achieves faster color change response, higher contrast, wider color change range and stronger aging resistance, while maintaining the long-term reliability of the material, and is suitable for a variety of smart devices and energy-saving buildings. In addition, the present invention also provides an electrochromic device, including but not limited to automobile rearview mirrors, automobile windows, aircraft portholes, building glass curtain walls, etc. These devices can automatically adjust the transmittance according to changes in ambient light to improve energy efficiency and user experience.

[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is:

[0006] An electrochromic material based on an organic skeleton structure, wherein the electrochromic material is a covalent organic skeleton material obtained by self-assembly reaction of a functional group containing a cathode electrochromic function and a functional group containing an anode electrochromic function by covalent bonding, and the covalent organic skeleton material has a chemical structure formula (I):

[0007] Wherein: R2 is a hydrocarbon functional group having 0 to 3 carbon atoms;

[0008] Y is a functional group containing an anode electrochromic function;

[0009] Z is a functional group comprising a cathode electrochromic function.

[0010] The inventors of the present application conceived of self-assembly reacting a functional group comprising a cathode electrochromic function and a functional group comprising an anode electrochromic function through C=N covalent bonding, thereby obtaining an electrochromic material having covalent organic skeleton structural characteristics, which has the characteristics of rapid response of existing phenazine and bipyridyl salt electrochromic materials, while also improving the structural stability and service life of the material.

[0011] As a preferred technical solution, the functional group containing the anode electrochromic function is a phenazine compound having a chemical structure of formula (II) or (III),

[0012] In the formula: R3 to R12 are independently selected from hydrogen, hydrocarbons having 1 to 20 carbon atoms, or oxygen-containing hydrocarbon functional groups.

[0013] As a preferred technical solution, the functional group containing the cathode electrochromic function is a bipyridyl salt compound having the chemical structure of formula (IV),

[0014] In the formula: R1 is a hydrocarbon or oxygen-containing hydrocarbon functional group having 1 to 20 carbon atoms;

[0015] R15 to R22 are each independently selected from hydrogen, methyl or ethyl;

[0016] X - For BF4 - , Cl - Br - PF6 - 、CH3COO - 、CH3C6H4SO3 - , C 12 H 25 C6H4SO3 -At least one of them.

[0017] As a preferred technical solution, the electrochromic material is first subjected to a substitution reaction between a monosubstituted bipyridyl salt and a bromoolefin aldehyde, and then subjected to an addition reaction with 1,3,5-tri(4-vinylphenyl)benzene to obtain an intermediate product containing a terminal aldehyde group; then the intermediate product is subjected to a molecular self-assembly reaction with phenazine diamine by covalent bonding.

[0018] As a preferred technical solution, the monosubstituted bipyridyl salt is obtained by a monosubstitution reaction between 4,4'-bipyridyl or a substituted 4,4'-bipyridyl compound and a bromoalkane or a bromoester.

[0019] As a preferred technical solution, the brominated alkanes include but are not limited to methyl bromide, ethyl bromide, propyl bromide, butyl bromide, pentane bromide, hexane bromide, heptane bromide, 1-bromooctane, 2-bromooctane, 3-bromooctane, 1-bromononane, 2-bromo-nonane, 1-bromo-7-methylnonane, 1-bromodecane, 1-bromode-2-methyldecane, 2-bromodecane, 3-bromodecane, 1-bromodeundecane, 2-bromodeundecane, 5-bromodeundecane, 5-(bromomethyl)undecane, 2-bromodedodecane, bromodedodecane, 1-bromodetridecane, 2-bromodetridecane, bromodetetradecane, 2-bromodedecane At least one of tetradecane, 7-(bromomethyl)pentadecane, 1-bromopentadecane, bromohexadecane, 1-bromo-2-methylhexadecane, 1-bromoheptadecane, bromoctadecane, 1-bromononadecane, and 1-bromoeicosane; the bromate ester includes but is not limited to at least one of undecyl 6-bromohexanoate, 2-bromodecane acid ethyl ester, 2-bromodecane acid undecyl ester, 11-bromodecane acid methyl ester, 11-bromodecane acid ethyl ester, 2-bromo-dodecanoic acid ethyl ester, 2-bromopropionic acid dodecyl ester, 16-bromo-hexadecanoic acid methyl ester, and 17-bromo-heptadecanoic acid methyl ester.

[0020] As a preferred technical solution, the brominated olefin aldehyde is 2-bromo-acrolein and / or 4-bromo-4-pentenal.

[0021] As a preferred technical solution, the phenazine diamine includes but is not limited to at least one of phenazine-1,9-diamine, 3,8-dimethylphenazine-2,7-diamine, phenazine-2,7-diamine, 3,8-dimethoxyphenazine-2,7-diamine, 3-methoxyphenazine-2,7-diamine, 1,3-phenazine diamine, and 1,4-phenazine diamine.

[0022] Another aspect of the present invention is to provide an electrochromic device, which includes a first conductive substrate, a second conductive substrate, and an electrochromic medium encapsulated between the first conductive substrate and the second conductive substrate, and the electrochromic medium includes at least one electrochromic material based on the organic skeleton structure as described above.

[0023] As a preferred technical solution, the electrochromic medium further includes at least one solvent; the solvent includes but is not limited to compounds that can be used as solvents, such as ethers, alcohols, nitriles, ketones, and esters. For example, ether substances include but are not limited to at least one of 3-methylcyclobutane sulfone, dimethyl sulfoxide, dimethylformamide, and tetraethylene glycol dimethyl ether; alcohol substances include but are not limited to ethoxyethanol; nitrile substances include but are not limited to at least one of acetonitrile, glutaronitrile, 3-hydroxypropionitrile, and 2-methylglutaronitrile; ketone substances include but are not limited to at least one of 2-acetylbutyrolactone and cyclopentanone; cyclic ester substances include but are not limited to at least one of β-propiolactone, γ-butyrolactone, and γ-valerolactone; cyclic carbonate substances include but are not limited to at least one of propylene carbonate (PC) and ethylene carbonate.

[0024] As a preferred technical solution, the electrochromic medium may include other materials, such as light absorbers, light (UV) stabilizers, heat stabilizers, antioxidants, cross-linked polymer matrices, self-supporting gels, and mixtures thereof.

[0025] As a preferred technical solution, the electrochromic device can be used as at least one of a car rearview mirror, a car window, an airplane porthole, and a building glass curtain wall.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The electrochromic material based on the organic skeleton structure of the present application innovatively combines the bipyridyl salt cathode electrochromic material and the phenazine anode electrochromic material to form an integrated electrochromic material with covalent organic skeleton structure characteristics, which not only takes into account the advantages of fast response speed of organic electrochromic materials, but also effectively avoids the density change of the color-changing material caused by electron transfer, the relative displacement of the cathode and anode color-changing materials, and other problems, thereby improving the overall stability and service life of the material, so that the electrochromic device can still maintain good performance after long-term use. In addition, this integrated design also enhances the material's aging resistance, allowing it to work reliably under various environmental conditions, thereby broadening the application scope of electrochromic technology in smart windows, car rearview mirrors, aircraft windows and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of the electrochromic material prepared in Example 1 of the present invention being formulated into an electrochromic medium solution and applied to the electrochromic anti-glare automobile rearview mirror lens of Application Example 1.

[0029] Figure 2 for Figure 1 Cross-sectional view of the electrochromic anti-glare automobile rearview mirror lens along the AA direction.

[0030] Figure 3 This is a schematic diagram of the electrochromic material prepared in Example 4 of the present invention being formulated into an electrochromic medium solution and applied to the electrochromic aircraft porthole intelligent device of Application Example 4.

[0031] Figure 4 for Figure 3 Cross-sectional view of the electrochromic aircraft window smart device along the BB direction. DETAILED DESCRIPTION

[0032] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0033] Example 1

[0034] The electrochromic material based on the organic skeleton structure of this embodiment is a covalent organic skeleton material obtained by self-assembly reaction of functional groups containing cathode electrochromic function and functional groups containing anode electrochromic function by covalent bonding, and the covalent organic skeleton material has the general chemical structure of formula (Ia):

[0035] Wherein: R2 is -(CH2)2-;

[0036] Y is a functional group containing an anode electrochromic function;

[0037] Z is a functional group comprising a cathode electrochromic function.

[0038] The functional group Y containing the anode electrochromic function is a phenazine compound having a chemical structure of formula (III-a),

[0039]

[0040] The functional group Z containing the cathode electrochromic function is a bipyridyl salt compound having the general chemical structure of formula (IV-a),

[0041] The preparation method of the electrochromic material described in this embodiment comprises the following steps:

[0042] S1: Dissolve 0.2 mol of 4,4'-bipyridine and 0.2 mol of ethyl bromide in 500 ml of acetonitrile solution, heat under reflux for 12 hours under stirring, then cool to room temperature and filter to obtain a 4-ethyl 4,4'-bipyridine salt derivative after mono-substitution reaction;

[0043] S2: 0.15 mol of the 4-ethyl 4,4'-bipyridinium salt derivative obtained in step S1 and 0.15 mol of 4-bromo-4-pentenal are dissolved in a mixed solution consisting of 250 ml of acetonitrile and 250 ml of dichloromethane, and a disubstituted reaction is carried out under the protection of a nitrogen atmosphere. After reacting for 12 hours, the solution is precipitated, and the solvent and unreacted by-products are filtered out. The filter cake is dissolved in water, and an anion exchange reaction is added with an aqueous solution of sodium hexafluorophosphate. The solution is precipitated again, and the precipitate is filtered and the filter cake is recrystallized to obtain a 4,4'-bipyridinium salt disubstituted derivative containing an unsaturated double bond and an aldehyde bifunctional group;

[0044] S3: 0.1 mol of the 4,4'-bipyridyl salt disubstituted derivative obtained in step S2 and 0.03 mol of 1,3,5-tri(4-vinylphenyl)benzene are dissolved in 500 ml of acetonitrile solution, and an appropriate amount of initiator azobisisobutyronitrile (AIBN) is added for addition reaction, the reaction temperature is controlled at 60-80°C, and the reaction time is 2 hours to obtain an intermediate product containing a terminal aldehyde group;

[0045] S4: 0.01 mol of the intermediate product obtained in step S3 and 0.012 mol of 3,8-dimethylphenazine-2,7-diamine are dissolved in 200 ml of ethanol solvent, and then 50 ml of a 20% potassium carbonate aqueous solution is added, heated to reflux for 8 hours, and a molecular self-assembly reaction is carried out by covalent bonding to obtain an electrochromic material based on an organic skeleton structure having a chemical structure of formula (Ia).

[0046] 0.5 g of the target product of the electrochromic material based on the organic skeleton structure was added to 50 ml of propylene carbonate solution containing 2.4 g of polymethyl methacrylate to prepare a 1# electrochromic medium solution.

[0047] Example 2

[0048] The raw materials and preparation method of the electrochromic material based on the organic skeleton structure of this embodiment are basically the same as those of Example 1, except that in the preparation method of the electrochromic material of this embodiment, step S1 uses 2,2',6,6'-tetramethyl-4,4'-bipyridine instead of 4,4'-bipyridine, bromohexane is used instead of bromoethane, step S2 uses sodium fluoroborate instead of sodium hexafluorophosphate, and step S4 uses 3,8-dimethoxyphenazine-2,7-diamine instead of 3,8-dimethylphenazine-2,7-diamine. Take 0.5g of the target product of the electrochromic material based on the organic skeleton structure of this embodiment, add it to 50ml of propylene carbonate solution dissolved with 2.4g of polymethyl methacrylate to prepare 2# electrochromic medium solution.

[0049] Example 3

[0050] The raw materials and preparation method of the electrochromic material based on the organic skeleton structure of this embodiment are basically the same as those of Example 1, except that in the preparation method of the electrochromic material of this embodiment, 2,2'-dimethyl-4,4'-bipyridine is used in step S1 instead of 4,4'-bipyridine, octadecane bromide is used instead of ethyl bromide, and phenazine-1,9-diamine is used in step S4 instead of 3,8-dimethylphenazine-2,7-diamine. Take 0.5g of the target product of the electrochromic material based on the organic skeleton structure of this embodiment, add it to 50ml of propylene carbonate solution dissolved with 2.4g of polymethyl methacrylate to prepare 3# electrochromic medium solution.

[0051] Example 4

[0052] The raw materials and preparation method of the electrochromic material based on the organic skeleton structure of this embodiment are basically the same as those of Example 1, except that in the preparation method of the electrochromic material of this embodiment, 2,2',6,6'-tetramethyl-4,4'-bipyridine is used in step S1 instead of 4,4'-bipyridine, undecyl 6-bromohexanoate is used instead of bromoethane, and phenazine-2,7-diamine is used in step S4 instead of 3,8-dimethylphenazine-2,7-diamine. 4.2g of the target product of the electrochromic material based on the organic skeleton structure of this embodiment is taken and added to 300ml of propylene carbonate solution dissolved with 20g of polymethyl methacrylate to prepare 4# electrochromic medium solution.

[0053] Example 5

[0054] The raw materials and preparation method of the electrochromic material based on the organic skeleton structure of this embodiment are basically the same as those of Example 1, except that in the preparation method of the electrochromic material of this embodiment, step S1 uses 2-bromopropionic acid dodecyl ester instead of ethyl bromide, step S2 uses sodium dodecylbenzene sulfonate instead of sodium hexafluorophosphate, and step S4 uses 3-methoxyphenazine-2,7-diamine instead of 3,8-dimethylphenazine-2,7-diamine. Take 4.2g of the target product of the electrochromic material based on the organic skeleton structure of this embodiment, add it to 300ml of propylene carbonate solution dissolved with 20g of polymethyl methacrylate to prepare 5# electrochromic medium solution.

[0055] Example 6

[0056] The raw materials and preparation method of the electrochromic material based on the organic skeleton structure of this embodiment are basically the same as those of Example 1, except that in the preparation method of the electrochromic material of this embodiment, step S1 uses 2,2'-dimethyl-4,4'-bipyridine instead of 4,4'-bipyridine, 16-bromo-hexadecanoic acid methyl ester is used instead of bromoethane, step S2 uses 2-bromo-acrolein instead of 4-bromo-4-pentenal, sodium toluenesulfonate is used instead of sodium hexafluorophosphate, and step S4 uses 1,4-phenazine diamine instead of 3,8-dimethylphenazine-2,7-diamine. Take 4.2g of the target product of the electrochromic material based on the organic skeleton structure of this embodiment, add it to 300ml propylene carbonate solution dissolved with 20g polymethyl methacrylate, and prepare 6# electrochromic medium solution.

[0057] Application Examples

[0058] The electrochromic device of the present application comprises a first conductive substrate, a second conductive substrate and an electrochromic medium encapsulated between the first conductive substrate and the second conductive substrate, wherein the electrochromic medium comprises at least one electrochromic material based on an organic skeleton structure as described above.

[0059] The manufacturing method of the electrochromic device is as follows:

[0060] A first substrate with a transparent conductive film coated on its surface and a second substrate with at least one conductive film coated on its surface are bonded together with frame glue, and then cured at high temperature to form a cavity, and a filling hole is left. The prepared electrochromic medium solution is poured into the filling hole, and then sealed with UV glue to obtain the electrochromic device.

[0061] As an example, the electrochromic device of the present application can be used as an electrochromic anti-glare automobile rearview mirror lens; it can also be used as an electrochromic aircraft window smart device; it can also be extended to various application scenarios such as automobile windows, building glass curtain walls, etc.

[0062] The present invention is further described by the following application examples.

[0063] Application Example 1

[0064] In this application example, Figure 1 and Figure 2As shown, a first glass substrate 1 coated with an ITO film 101 (150 nm thick) and a second glass substrate 2 coated with a 120 nm titanium dioxide / 80 nm silicon dioxide / 120 nm titanium dioxide / 10 nm silver laminated film 201 are bonded together with a frame glue 3, and then baked at 120° C. for 1 hour to form a cavity 4, and a perfusion hole 301 is left. 1# electrochromic medium solution 5 is poured into the perfusion hole 301, and then sealed with UV glue to obtain an electrochromic anti-glare automobile rearview mirror lens 1001 with a length and width of 15 cm×25 cm.

[0065] The test results show that the electrochromic anti-glare automobile rearview mirror lens 1001 obtained in this application example has a maximum reflectivity of 46.1% and a minimum reflectivity of 6.3%; the response time for the reflectivity to decrease from 40% to 15% (i.e., coloring time) is 3S, and the response time for the reflectivity to decrease from 15% to 40% (i.e., fading time) is 4S; after 50,000 times of electrical cycle test with 1.2V power supply, the color change depth and color change speed of the 1# electrochromic medium solution 5 did not show obvious degradation.

[0066] Application Example 2

[0067] In this application example, a first glass substrate coated with an ITO film (150 nm thick) and a second glass substrate coated with 120 nm titanium dioxide / 80 nm silicon dioxide / 120 nm titanium dioxide / 10 nm silver laminated films are bonded together with frame glue, and then baked at 120°C for 1 hour to form a cavity and leave a perfusion hole. A 2# electrochromic medium solution is poured into the perfusion hole, and then sealed with UV glue to obtain an electrochromic anti-glare automobile rearview mirror lens with a length and width of 15 cm×25 cm.

[0068] The test results show that the electrochromic anti-glare automobile rearview mirror lens obtained in this application example has a maximum reflectivity of 45.2% and a minimum reflectivity of 6.9%; the response time for the reflectivity to decrease from 40% to 15% (i.e., coloring time) is 3S, and the response time for the reflectivity to decrease from 15% to 40% (i.e., fading time) is 4S; after 50,000 times of electrical cycle test with 1.2V power supply, the color change depth and color change speed of the 2# electrochromic medium solution did not show obvious degradation.

[0069] Application Example 3

[0070] In this application example, a first glass substrate coated with an ITO film (150 nm thick) and a second glass substrate coated with 120 nm titanium dioxide / 80 nm silicon dioxide / 120 nm titanium dioxide / 10 nm silver laminated films are bonded together with frame glue, and then baked at 120°C for 1 hour to form a cavity and leave a perfusion hole. 3# electrochromic medium solution is poured into the perfusion hole, and then sealed with UV glue to obtain an electrochromic anti-glare automobile rearview mirror lens with a length and width of 15 cm×25 cm.

[0071] The test results show that the electrochromic anti-glare automobile rearview mirror lens obtained in this application example has a maximum reflectivity of 44.8% and a minimum reflectivity of 7.2%; the response time for the reflectivity to decrease from 40% to 15% (i.e., coloring time) is 3S, and the response time for the reflectivity to decrease from 15% to 40% (i.e., fading time) is 4S; after 50,000 times of electrical cycle test with 1.2V power supply, the color change depth and color change speed of the 3# electrochromic medium solution did not show obvious degradation.

[0072] Application Example 4

[0073] In this application example, Figure 3 and Figure 4 As shown, a first glass substrate 1 coated with an ITO film 101 (150 nm thick) and a second glass substrate 2 coated with an ITO film 201 (150 nm thick) are bonded together with a frame glue 3, and then baked at 120° C. for 1 hour to form a cavity 4, and a perfusion hole 301 is left. A 4# electrochromic medium solution 5 is poured into the perfusion hole 301, and then sealed with UV glue to obtain an electrochromic aircraft window smart device 2001 with a length and width of 25 cm×40 cm.

[0074] The test results show that the electrochromic aircraft window intelligent device 2001 obtained in this application example has a transparent state transmittance of 87.2% and a colored state transmittance of 1.6%; the response time for the transmittance to decrease from 60% to 5% (i.e., the coloring time) is 35S, and the response time for the transmittance to decrease from 5% to 60% (i.e., the fading time) is 42S; after 20,000 times of electric cycle test with 1.2V power supply, the color change depth and color change speed of the 4# electrochromic medium solution did not show obvious degradation; in the aging box, 280-400nm ultraviolet lamp was used for aging operation, and the aging time was greater than 168h.

[0075] Application Example 5

[0076] In this application example, a first glass substrate coated with an ITO film (150 nm thick) and a second glass substrate coated with an ITO film (150 nm thick) are bonded together with frame glue, and then baked at 120°C for 1 hour to form a cavity and leave a perfusion hole. 5# electrochromic medium solution is poured into the perfusion hole, and then sealed with UV glue to obtain an electrochromic aircraft window smart device with a length and width of 25 cm × 40 cm.

[0077] The test results show that the electrochromic aircraft window intelligent device obtained in this application example has a transparent state transmittance of 86.8% and a colored state transmittance of 1.5%; the response time for the transmittance to decrease from 60% to 5% (i.e., the coloring time) is 33S, and the response time for the transmittance to decrease from 5% to 60% (i.e., the fading time) is 40S; after 20,000 times of electrical cycle test at 1.2V, the color change depth and color change speed of the 5# electrochromic medium solution did not show obvious degradation; in the aging box, 280-400nm ultraviolet lamp was used for aging operation, and the aging time was greater than 168h.

[0078] Application Example 6

[0079] In this application example, a first glass substrate coated with an ITO film (150 nm thick) and a second glass substrate coated with an ITO film (150 nm thick) are bonded together with frame glue, and then baked at 120°C for 1 hour to form a cavity and leave a perfusion hole. 6# electrochromic medium solution is poured into the perfusion hole, and then sealed with UV glue to obtain an electrochromic aircraft window smart device with a length and width of 25 cm × 40 cm.

[0080] The test results show that the electrochromic aircraft window intelligent device obtained in this application example has a transparent state transmittance of 87.5% and a colored state transmittance of 1.6%; the response time for the transmittance to decrease from 60% to 5% (i.e., the coloring time) is 37S, and the response time for the transmittance to decrease from 5% to 60% (i.e., the fading time) is 43S; after 20,000 times of electrical cycle test at 1.2V, the color change depth and color change speed of the 6# electrochromic medium solution did not show obvious degradation; in the aging box, 280-400nm ultraviolet lamp was used for aging operation, and the aging time was greater than 168h.

[0081] It can be seen that the patent of the present invention has considerable advantages over the currently used technology. The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may have various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention to be protected.

Claims

1. An electrochromic material based on an organic skeleton structure, characterized in that: The electrochromic material is a covalent organic framework material obtained by self-assembly reaction of a functional group containing a cathode electrochromic function and a functional group containing an anode electrochromic function through covalent bonding, and the covalent organic framework material has a general chemical structure of formula (I): In the formula: R2 is a hydrocarbon functional group having 0 to 3 carbon atoms; Y is a functional group containing an anode electrochromic function; Z is a functional group comprising a cathode electrochromic function.

2. The electrochromic material based on an organic skeleton structure as claimed in claim 1, characterized in that: The functional group containing the anode electrochromic function is a phenazine compound having a general chemical structure of formula (II) or (III), In the formula: R3 to R12 are independently selected from hydrogen, hydrocarbons having 1 to 20 carbon atoms, or oxygen-containing hydrocarbon functional groups.

3. The electrochromic material based on an organic skeleton structure as claimed in claim 1, characterized in that: The functional group containing cathode electrochromic function is a bipyridyl salt compound having a chemical structure of formula (IV), In the formula: R1 is a hydrocarbon or oxygen-containing hydrocarbon functional group having 1 to 20 carbon atoms; R15 to R22 are each independently selected from hydrogen, methyl or ethyl; X - For BF4 - , Cl - Br - PF6 - 、CH3COO - 、CH3C6H4SO3 - , C 12 H 25 C6H4SO3 - At least one of them.

4. The electrochromic material based on an organic skeleton structure according to claim 1, characterized in that: The electrochromic material is first subjected to a substitution reaction between a monosubstituted bipyridyl salt and a bromoolefin aldehyde, and then subjected to an addition reaction with 1,3,5-tri(4-vinylphenyl)benzene to obtain an intermediate product containing a terminal aldehyde group; and then the intermediate product is subjected to a molecular self-assembly reaction with phenazine diamine by covalent bonding.

5. The electrochromic material based on an organic skeleton structure as claimed in claim 4, characterized in that: The monosubstituted bipyridyl salt is obtained by monosubstituting 4,4'-bipyridyl or a substituted 4,4'-bipyridyl compound with a bromoalkane or a bromoester.

6. The electrochromic material based on an organic skeleton structure as claimed in claim 5, characterized in that: The brominated alkanes include, but are not limited to, methyl bromide, ethyl bromide, propane bromide, butyl bromide, pentane bromide, hexane bromide, heptane bromide, 1-bromooctane, 2-bromooctane, 3-bromooctane, 1-bromononane, 2-bromo-nonane, 1-bromo-7-methylnonane, 1-bromodecane, 1-bromode-2-methyldecane, 2-bromodecane, 3-bromodecane, 1-bromodeundecane, 2-bromodeundecane, 5-bromodeundecane, 5-(bromomethyl)undecane, 2-bromodedodecane, bromodedodecane, 1-bromodetridecane, 2-bromodetridecane, bromodetetradecane, 2-bromodetetradecane, 7-bromodedecane, 1-bromodeundecane, 2-bromodeundecane, 5-bromodeundecane, 5-(bromomethyl)undecane, 2-bromodedodecane, 2-bromodedodecane, 2-bromodedodecane, 2-bromodetridecane, 2-bromodetetradecane, 2-bromodetetradecane, 2-bromodetetradecane, 2-bromodedo ... At least one of (bromomethyl)pentadecane, 1-bromopentadecane, bromohexadecane, 1-bromo-2-methylhexadecane, 1-bromoheptadecane, bromooctadecane, 1-bromononadecane, and 1-bromoeicosane; the bromate ester includes but is not limited to at least one of undecyl 6-bromohexanoate, 2-bromoundecanoic acid ethyl ester, 2-bromoacetate undecyl ester, 11-bromoundecanoic acid methyl ester, 11-bromoundecanoic acid ethyl ester, 2-bromo-dodecanoic acid ethyl ester, 2-bromopropionic acid dodecyl ester, 16-bromo-hexadecanoic acid methyl ester, and 17-bromo-heptadecanoic acid methyl ester.

7. The electrochromic material based on an organic skeleton structure as claimed in claim 4, characterized in that: The brominated olefin aldehyde is 2-bromo-acrolein and / or 4-bromo-4-pentenal.

8. The electrochromic material based on an organic skeleton structure as claimed in claim 4, characterized in that: The phenazine diamine includes but is not limited to at least one of phenazine-1,9-diamine, 3,8-dimethylphenazine-2,7-diamine, phenazine-2,7-diamine, 3,8-dimethoxyphenazine-2,7-diamine, 3-methoxyphenazine-2,7-diamine, 1,3-phenazine diamine, and 1,4-phenazine diamine.

9. An electrochromic device, characterized in that: The electrochromic device comprises a first conductive substrate, a second conductive substrate and an electrochromic medium encapsulated between the first conductive substrate and the second conductive substrate, wherein the electrochromic medium comprises at least one electrochromic material based on an organic skeleton structure as claimed in any one of claims 1 to 8.

10. The electrochromic device according to claim 9, characterized in that: The electrochromic device can be used as at least one of a car rearview mirror, a car window, an airplane porthole, and a building glass curtain wall.